Feeding Artemia nauplii enriched with the probiotic bacterium Bacillus subtilis improved growth performance, survival and digestive enzyme activity of Clarias batrachus (Linnaeus, 1758) larvae - Kamble, S. P.; Sahu, A. K.; Mohanty, S.; Sahoo, S. K.; Murmu, K.; Prakash, Chandra; Chadha, N. K. (Indian Journal of Fisheries, 2019)
Clarias batrachus (Linnaeus, 1758) larvae were subjected to different modes of probiotic (Bacillus subtilis) administration such as:  T1: feeding Artemia nauplii enriched with B. subtilis; T2: feeding enriched Artemia nauplii + addition of B. subtilis in water  and T3: addition of B. subtilis in water alone, for a period of 14 days. A control group (T0) with no probiotic administration was also maintained. On termination of the experiment, probiotic supplemented through enriched Artemia nauplii along with addition in  water (T2) yielded significantly (p0.05) between T1 and T2. Similar trend was observed in the case of total gut bacterial count and digestive enzyme activity. The highest (p0.05) difference was observed between T2 and T1. The present study reiterated the advantage of B. subtilis, and its administration through enriched Artemia nauplii which could be a promising supplementation mode during   C. batrachus larval rearing. Keywords: Growth, Larval rearing, Magur, Probiotic, Survival